6 - Migrants volontaires et migrants citoyens : les recompositions des associations de migrants originaires de la région de Kayes (Mali) - Lima, Stéphanie (Africa Development, 2021)
In the Senegal River Basin, the involvement of migrants in their home region has a long history built on the relations between countries of origin and host countries. In the case of Mali, decentralization, municipal zoning and the advent of local democracy have met the expectations of migrants who report, insofar as they have for decades funded utilities. Faced with an absent state, migrants, despite the distance, have mitigated this disengagement. In the region of Kayes, the management of local affairs is now in the hands of local councillors, some of whom are ex-migrants. For these councillors looking for partners, migrants have been identified as privileged interlocutors. On their side, with a rather surprising response, migrants have created an additional layer in the social fabric, with the establishment of community associations. In this context, they also engage in dialogue with elected officials and people on local development projects, with a view to renegotiate their role, including access to local citizenship.